Blastocystis presence alters gut archaeal communities and metabolic functions in Tibetan antelopes (Pantholops hodgsonii) - Su, Jin-Wen; Qin, Si-Yuan; Liu, Jian; Lei, Cong-Cong; Zhang, Xiao-Tian; Shi, Wen-Hui; Xie, Lin-Hong; Liu, Yan; Ni, Hong-Bo; Yu, Ming-Yuan; Liang, Hong-Rui; Qin, Ya; et al. (Frontiers in Veterinary Science, 2025)
BackgroundArchaea are vital members of the gut microbiota, yet their diversity and functions in high-altitude wildlife remain poorly understood. Understanding their ecological roles can provide insights into host health and microbial community dynamics.MethodsWe applied metagenome-assembled genome (MAG)-based approaches to investigate gut archaea in Tibetan antelopes (Pantholops hodgsonii) and assess their shifts in the presence of Blastocystis. A total of 463 non-redundant archaeal MAGs were reconstructed and analyzed for taxonomic diversity and functional potential.ResultsThe MAGs encompassed 16,189 protein clusters, with over 70% representing potentially novel species, highlighting substantial unexplored archaeal diversity. Alpha diversity showed no significant differences between healthy and Blastocystis-present groups, but beta diversity analysis revealed marked community restructuring, including decreased Methanobacteriota and increased Halobacteriota and Thermoplasmatota in the Blastocystis-present group. Functional annotation indicated changes in energy and nucleotide metabolism and alterations in carbohydrate-active enzyme composition. Additionally, putative viral sequences were detected within archaeal MAGs, suggesting potential virus-microbe interactions.ConclusionOur findings provide novel insights into the diversity and ecological functions of gut archaea in Tibetan antelopes, offering a foundation for future research on their contributions to host health and microbial ecology.